Labour absorption in Hongkong and Singapore since 1970 - Fong, Pang Eng; Pew, Ong Nai (The Philippine Review of Business and Economics, 1988)
Based on census data, this paper traces the labour absorption pattern in the city-economies of Hong Kong and Singapore since the early 1970s to the early 1980s. Among the similarities highlighted are the export-led growth in the 1970s, the shift towards higher valued activities, the simultaneous expansion of the labor force and employment, an unprecedented increase in female labor force inflow, the more efficient use of manpower due to rapid output growth, and the preponderance of the more export-oriented manufacturing industries contributing the bulk of new jobs. On the other hand, one significant difference in this sectoral pattems of labor absorption is that, compared to Singapore, Hong Kong's ratio of employment growth to output was higher in commerce and lower in manufacturing due to the greater supply-induced employment-creation. The higher labor absorption rate in Singapore manufacturing relative to that of Hong Kong is most likely because of the greater influence of the former's government on the labor market as well as the influx of labor intensive foreign manufacturing firms. The paper notes the increasing similarity in the early 1980s between the the two economies as well as the increasing convergence of government perception of its role in both city-economies.